THÀNH PHẦN LOÀI VÀ MẬT ĐỘ THỰC VẬT NỔI Ở HỒ CHỨA ĐẮK R’TANG, TỈNH ĐẮK NÔNG - Nguyễn, Thị Thuý; Trần, Văn Phước; Trương, Thị Bích Hồng; Nguyễn, Văn Quỳnh Bôi (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
SPECIES COMPOSITION AND DENSITY OF PHYTOPLANKTON IN DAK R’TANG RESERVOIR IN DAK NONG PROVINCEA study on the composition and density of phytoplankton in Dak R’Tang reservoir of Dak Nong province was conducted in the period from March to December, 2014. A total of 109 phytoplankton species of 5 phyla was found. The numbers of species and their propotion in the total for Chlorophyta, Cyanophytta, Heterokontopphyta, Dinophyta and Euglenophyta are 46 species (42.20%), 23 species (21.10%), species 17(15.60%), 13(11.93%) and 10 species (9.17%), respectively.In interfering season, the number of species identified was the highest with 64 species, in dry season it was 54 species, and in rainy season - 37 species.The density of phytoplankton was the highest 1,161,000 cells/l in the interfering season, in dry season it was 989,000 cells/l, and in rainy season - 853,000 cells/l.